Implicaciones de bienestar en el sector residencial de la unificación tarifaria en el servicio de electricidad en el departamento de Antioquia (2008)
In the Department of Antioquia a change was evidenced in the welfare level of its citizens because the unification of the price service of electricity due to EPM acquired the 100% of the EADE’s shares. Specifically, the new price service implied a rise in the welfare of 3.21% at aggregated level. However, the changes in the welfare level are too heterogeneous when the data is seen by income level and location. For example, households with lower income and outside the metropolitan area increased their welfare level 20%, whereas households in this area and with higher income raised their welfare 6%. In the metropolitan area, the households with lower income increased their welfare 4%, while the families with higher income experienced a loss of 1.4% in their welfare level. These results are found due to the demand’s price and income elasticities that were estimated for the Department; -0.32 and 0.72, respectively. It is important to realize that demand’s price elasticities are increasing with stratum, while the demand’s income elasticities are decreasing. Additionally, the short term elasticities are smaller than long term, the demand for electricity has a stationary effect in the fourth quarter and there is no effect due to substitute services. Finally, a simulated scenario that implies a change in the national legal field shows that it is possible to obtain better distributional effects and higher increments at aggregated level in the welfare without a detriment in the financial position of the firm.